Synthesis of anatase TiO2 rods with dominant reactive {010} facets for the photoreduction of CO2 to CH4 and use in dye-sensitized solar cells - Pan, Jian; Wu, X.; Wang, L.; Liu, G.; Lu, G.; Cheng, H. (2011)
Single crystalline anatase TiO2 rods with dominant reactive {010} facets are directly synthesized by hydrothermally treating Cs 0.68Ti1.83O4/H0.68Ti 1.83O4 particles. The nanosized rods show a comparable conversion efficiency in dye-sensitized solar cells (DSSCs), and a superior photocatalytic conversion of CO2 into methane to the benchmark P25 TiO2 nanocrystals. © 2011 The Royal Society of Chemistry.